(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Iron oxide (α-Fe2O3) nanoparticles were fabricated by chemical precipitation and Eco-Friendly routes, using Capparis Spinosa leaves extract, sodium hydroxide and iron sulphate heptahydrous. The calcination temperature for α-Fe2O3 nanoparticles was at 600 °C. All prepared samples were investigated using different physical methods such as XRD, FT-IR, FESEM, EDX and DLS. The XRD analysis confirmed that all the prepared nanoparticles consist only hematite phase with the size of 31.95 nm and 26.92 nm for chemical precipitation and Eco-Friendly method respectively. The α-Fe2O3 nanoparticles in the FESEM image showed a spherical nanoparticle structure. The EDX results presented the elements content (Fe = 64.3, O= 24.6) by green synthesis and (Fe = 66.3, O= 29.3) through chemical method. The distribution of iron oxide nanoparticles prepared via the Eco-Friendly method was greater as compared to the chemical precipitation method according to DLS analysis.